A percepção de práticas de responsabilidade social e valores éticos corporativos no comprometimento organizacional e satisfação no trabalho em uma instituição bancária - Penha, Emanuel Dheison dos Santos (2015)
This study aims to analyze the influence of the perception of Practice for Corporate Social Responsibility (PCSR) and Ethical Values Corporative (EVC) on Job Satisfaction (JS) and Organizational Commitment (OC) of employees of a financial institution, installed on state of Ceará. The research had the following objectives to investigate the influence of corporate ethical values in job satisfaction; check the influence of corporate ethical values in organizational commitment; evaluate the influence of corporate ethical values in the perception of Corporate Social Responsibility Practices (CSR); investigate the influence of the perception of CSR practices in job satisfaction; check the influence of the perception of CSR practices in organizational commitment; evaluate the relationship between job satisfaction and organizational commitment; assess the influence of sociodemographic variables in the perception of corporate social responsibility practices in organizational commitment, the perception of corporate ethical values and job satisfaction. The research is quantitative held by a case study. Appealed to the exploratory and confirmatory factor analysis to validate the scales, the structural equation model for confirming the assumptions and techniques univariate and multivariate to verify the effect of sociodemographic variables in the constructs. The hypotheses of the research studies are: corporate ethical values positively influence job satisfaction; corporate ethical values positively influence organizational commitment; corporate ethical values positively influence the perception of corporate social responsibility practices of employees; the perception of CSR positively influences job satisfaction; the perception of corporate social responsibility practices positively influence the organizational commitment; there is a positive correlation between job satisfaction and organizational commitment; employees and volunteers have higher satisfaction levels at work, perception of social responsibility practices Corporate and Organizational Commitment. The results show that the accession of the company to ethical and socially responsible behavior positively affects job satisfaction and organizational commitment of employees. Logo, business investments that want to keep their committed and satisfied employees, should attach importance to the development and effective dissemination of a code of ethics, as well as the accession of CSR practices. Another point highlighted was that participating employees of any bank volunteer program have better rates of PRSC, CO and ST. Therefore, develop, disseminate and put into practice volunteer programs in the organization can generate competitive advantage in business because they help retain talent. It was also found that VEC prior to PRSC; the PRSC positively affect the CO and ST of respondents. So, for your employees, socially responsible company appearance passes by the realization company is ethical. The results also show that employees who occupy higher positions had average rates of greater awareness for the four constructs, and the charge of socio-demographic variable that most influenced the perception indices. The limitations of the research, it has not representativeness of the sample, the presence of many outliers, the questionnaire directly in the organization and the fact that the structural equation model can’t ensure a relationship of cause and effect. For future research, it is suggested to replicate the study in a larger population at national level, in a probabilistic sample in an approach of mixed methods.